KAJIAN DIALEKTOLOGIS TERHADAP VARIASI LAHJAH ARABIYAH: MENYINGKAP KERAGAMAN LINGUISTIK DAN BUDAYA - Pabbajah, M. Taufiq Hidayat; Ramli, Kaharuddin; Fauziah, St. (Al-Fakkaar, 2024)
This research focuses on the identification and analysis of dialectal variations (lahjah) in the Arabic language through a literature review approach that includes various printed books and scholarly journal articles. The study examines the main linguistic characteristics that distinguish Arabic dialects, covering phonetic, morphological, syntactic, and lexical differences. Additionally, this research explores the influence of socio-cultural factors on dialect variation. The findings indicate that there are numerous dialectal variations in Arabic, including both major and local dialects, demonstrating that Arabic dialects are highly complex and influenced by various geographical and socio-cultural factors. The findings of this research make a significant contribution to the understanding of linguistic and cultural diversity in the Arabic language as well as the linguistic and social dynamics of Arabic dialects. The conclusion of this study underscores the importance of considering socio-cultural contexts in dialectal analysis. This research also acknowledges limitations regarding the sources of data, which are confined to existing literature, and recommends further field research to gain a deeper and more comprehensive understanding.